Clergy self-care finding a balance for effective ministry - Oswald, Roy M. (New York, NY Alban Institute, 1995)
Includes bibliographical references.
Published in association with Ministers Life - A Mutual Life Insurance Company
Keywords: Clergy -- psychology; Clergy -- job stress; Burn out (psychology).